Dual-band circularly polarized flat antenna with plano convex and concave slots for RFID readers - Prawate Wongsakulphasatch; Chuwong Phongcharoenpanich (My University, 2017)
This article has proposed a circularly polarized dual-band antenna with unidirectional pattern operating at the bandwidth frequencies of 920–925 MHz and 2.40–2.48 GHz for radiofrequency identification (RFID) readers. The proposed antenna structure is of a radiating patch with a single feeder and two pairs of plano convex and concave slots. This work has innovated and utilized the convex and concave slotting technique to generate the circular polarization. The simulated results showed that the dual-band antenna is of circular polarization (CP) and unidirectional radiation pattern with the 3 dB axial ratio and the respective gains of 1.31 and 1.36 dBic for the experimental lower and upper bandwidth frequencies. An antenna prototype was subsequently fabricated and tests performed. The simulated and measured results are in good agreement, rendering the proposed dual-band antenna with plano convex and concave slots suitably applicable to the ultrahigh frequency and microwave RFID readers.
Keywords: Multi-band device; Turnstile antenna; Antenna Design and Analysis